Kontradiksi Putusan Judicial Review Mahkamah Konstitusi dan Mahkamah Agung dalam Sistem Ketatanegaraan Indonesia - Sunardi, Dian (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2022)
Based on the Republic of Indonesia Constitution, 1945, the authority of judicial review in Indonesia is currently held by two judicial institutions, the Supreme Court and the Constitutional Court. One of the problems raised from this overlapping jurisdiction between the two institutions is the disparity in judicial review decisions, and they even tend to be contradictory. The purpose of this paper is to analyze the background of the issue regarding the cause of the contradiction that arises from the judicial review decision of the Supreme Court and the judicial review decision of the Constitutional Court. The research methodology in this writing uses the normative juridical method, namely by describing problems through literature and regulations related to the problem.Â The conclusions obtained in this paper are: the cause of the contradiction of the judicial review decisions of the Supreme Court and the Constitutional Court is due to the equality of the two institutions, the absence of legal provisions that require the Supreme Court to conduct judicial reviews to refer to the judicial review decisions of the Constitutional Court and the application of the principle of freedom for judges in conducting judicial proceedings. There are several concepts to answer the problem, namely: giving the sole judicial review authority to the Constitutional Court, or eliminating the Constitutional Court so that the judicial review authority is back to the Supreme Court.Pengujian undang-undang merupakan suatu hal baru dalam praktik ketatanegaraan Indonesia. Kewenangan judicial review saat ini diemban oleh dua lembaga yudikatif yakni Mahkamah Agung dan Mahkamah Konstitusi. Putusan-putusan hasil judicial review yang dilakukan oleh kedua lembaga tersebut tidak luput dari permasalahan, seperti adanya kontradiksi antara putusan judicial review dari kedua lembaga. Tujuan dari penulisan ini adalah untuk menganalisis latarbelakang permasalahan berkenaan dengan sebab terjadinya kontradiksi yang muncul dari putusan judicial review Mahkamah Agung dan putusan judicial review Mahkamah Konstitusi. Adapun metodologi penelitian dalam penulisan ini mengÂgunakan metode yuridis normatif yakni dengan menggambarkan permasalahan melalui kepustakaan dan peraturan yang berhubungan dengan permasalahan. Adapun kesimpulan yang diperoleh dalam penulisan ini yakni: sebab terjadinya kontradiksi putusan judicial review Mahkamah Agung dan Mahkamah Konstitusi diakibatkan kesetaraan kedua lembaga, belum adanya ketentuan hukum yang mewajibakan Mahkamah Agung dalam melakukan judicial review merujuk pada putusan judicial review Mahkamah Konstitusi dan penerapan asas bebas bagi hakim dalam melakukan proses peradilan. Terdapat beberapa konsep untuk menajwab permasalahan yakni: penggabungan satu atap kewenangan Judicial review di Mahkamah Konstitusi sebagai lembaga court of law secara utuh; menghilangkan kelembagaan Mahkamah Konstitusi sehingga kewenangan judicial review berada di Mahkamah Agung dan menjadikan Mahkamah Agung sebagai satu-satunya pemegang kekuasaan kehakiman.